(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Agnikarma has been one of the peculiar parasurgical procedures described in Sushrut Samhita. The most important indication of Agnikarma is when there is bleeding from vessel or diseases in which bleeding is expected. Technology and instruments used for hemostasis now a days differ from ancient ones. However fundamental principle of heating the tissues remains same which is widely used in present era. Earlier rods (shalaka) made from different metals were used for burning out bleeding veins. Red hot shalaka was applied on tissues and bleeders so that contraction of vessels occurs. So hemostasis was achieved by cauterization of tissues at high temperature. With advancement of technology in bio-medical engineering various machines like Electrocautery, Infrared coagulation, Electrosurgical unit (high frequency and low frequency) and LASERs were invented for similar purpose. In Electrocautery electrical current is used to heat a metal wire to burn or coagulate the specific area of tissue. In Electrosurgical unit alternating current is passed through tissue and heat is created by the resistance of tissue to current. Electrodes are used to cut, coagulate or even fuse the tissue. IRC involves the use of infrared light as a heat source to coagulate vessels supplying blood. Lasers are used to ablate the veins in which amplified light energy is used to generate heat. Tissue dehydration, protein coagulation and vaporization are the processes involved in achieving hemostasis. Working principles and energy sources used in these devices vary from each other; however the hemostasis is achieved by common fundamental principle i.e. generating heat which is similar to Agnikarma.